Design, modeling, and optimization of 3D printed compliant mechanisms with applications to miniature walking robots - DeMario, Anthony R., author; Zhao, Jianguo, advisor; Stansloski, Mitchell, committee member; Maciejewski, Anthony, committee member (Colorado State University. Libraries, 2018)
Miniature robots have many applications ranging from military surveillance to search and rescue assistance in disaster areas. Traditionally, fabrication of these robots has been labor intensive, time-consuming, and expensive. This thesis proposes to leverage recent advances in 3D printing technology to fabricate centimeter-scale walking robots utilizing compliant elements printed directly into the walking mechanisms in replacement of traditional revolute joints or rigid links. The ability to design around the capabilities of 3D printers and novel material choices gives miniature robots the ability to have multiple functions in the same mechanism, reduces the overall number of parts that must be assembled to make a functional robot, and decrease the time and cost of prototyping. This thesis details three areas of study for compliant mechanisms with applications to walking robots. First, we utilize multi-material 3D printing to fabricate a miniature walking robot (49 x 38 x 25mm) that directly replaces the traditional revolute joints in the designed walking mechanism with a custom, soft joint. Some links are also printed with soft materials to enhance the robustness and durability of the robot. Along with design and testing of the robot, we develop two numerical models to simulate the effects of the soft elements on the mechanism trajectory. Second, we leverage the numerical models to optimize the design of the walking mechanism to produce a trajectory similar to that of the same mechanism using all revolute joints. Third, we redesign the original robot to utilize a conductive polylactic acid (PLA) material to 3D print linkages that allow for changing joints locations by softening the desired part through applied electricity. This variable joint mechanism can create multiple trajectories without changing the mechanical structure, therefore creating a multi-functional compliant mechianism. Such capabilities are demonstrated throughwalking on the ground and grasping objects using the same leg mechanism.
Keywords: mechanism optimization; multi-material 3D printed; adaptive 3D printed mechanisms; non-linear robot kinematics; miniature walking robots